A Path Analysis of Leadership, Organizational Culture, Job Satisfaction Intervention, and Employee Performance - Rudi Wibowo; Suyitno Suyitno; Fais Wahidatul Arifatin; Adi Lukman Hakim (Universitas Negeri Surabaya, 2025)
Numerous variables continue to contribute to the reduction in staff performance at Community Health Centers. By using employee job satisfaction interventions as health care interventions, this study seeks to examine the effects of organizational leadership and culture on service performance. A total of 47 respondents were sampled for this quantitative descriptive study. According to the research's findings, job satisfaction is one way that leadership and organizational culture have a positive and significant impact on employee performance. Leadership and organizational culture also have a positive and significant impact on employee performance.